2015
DOI: 10.5664/jcsm.4462
|View full text |Cite
|
Sign up to set email alerts
|

Night-to-night Variability in Obstructive Sleep Apnea Severity: Relationship to Overnight Rostral Fluid Shift

Abstract: Study Objectives: Overnight rostral fl uid shift from the legs to the neck may narrow the pharynx and contribute to obstructive sleep apnea (OSA) pathogenesis. We hypothesized that night-to-night changes in the apneahypopnea index (AHI) would be associated with changes in overnight rostral fl uid shift. Methods: Twenty-six patients with OSA (AHI ≥ 10) underwent two polysomnograms 14 days apart with measurement of neck and leg fl uid volumes (LFV), neck circumference and upper-airway cross-sectional area before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 34 publications
3
44
1
1
Order By: Relevance
“…In addition to the above mechanisms, rostral fluid shifts may con- overload states (Table 4) (Redolfi et al, 2009;White, Lyons, Yadollahi, Ryan, & Bradley, 2015a,2015bYadollahi et al, 2015;Yumino et al, 2010). In this study, we demonstrated greater ECFV shifts in the PH subjects compared with previous studies in the healthy population .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition to the above mechanisms, rostral fluid shifts may con- overload states (Table 4) (Redolfi et al, 2009;White, Lyons, Yadollahi, Ryan, & Bradley, 2015a,2015bYadollahi et al, 2015;Yumino et al, 2010). In this study, we demonstrated greater ECFV shifts in the PH subjects compared with previous studies in the healthy population .…”
Section: Discussionsupporting
confidence: 52%
“…In addition to the above mechanisms, rostral fluid shifts may contribute to the pathogenesis of SA or modulate the type of SA. In support of this hypothesis, overnight ECFV shifts have been demonstrated in otherwise healthy SA subjects, and in those with fluid overload states (Table ) (Redolfi et al., ; White, Lyons, Yadollahi, Ryan, & Bradley, ,; Yadollahi et al., ; Yumino et al., ). In this study, we demonstrated greater ECFV shifts in the PH subjects compared with previous studies in the healthy population (Yadollahi et al., ).…”
Section: Discussionmentioning
confidence: 86%
“…We chose this threshold because a change in AHI higher than 20 events·h −1 is considered generally beyond normal night-to-night variability [23, 24] and the improvement is more likely due to the medication effect. Using this criterion, we identified five responders (dashed line in the graphs in figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical significance of this difference remains to be established. Nonetheless, previous work documents the role of night-to-night variability as a factor in obstructive sleep apnea 37 , individual differences in sleep quality 38 , and responsiveness to treatment 39 . Future work with older adults, including those with OA, clearly should examine other predictors of individual variability over multiple nights, as well as the association of variability with physical (e.g., fatigue, weight gain) and mental health outcomes (e.g., anxiety, depression).…”
Section: Discussionmentioning
confidence: 99%